Building our house [videorecording (DVD)] - Bean, Jonathan, 1979-; Floyd, Jacquie, 1975- (Dreamscape Media, 2013)
Mom and Dad are going to make the new house themselves, from the ground up. From empty lot to finished home, every stage of their year-and-a-half-long building project is here. And at every step their lucky kids are watching and getting their hands dirty, in page after page brimming with machines, vehicles, and all kinds of house-making activities! As he imagines it through the eyes of his older sister, this is Jonathan Bean's retelling of his own family's true experience.